The Isolationist Downfall with the Establishment of the Truman Doctrine - Yamada, Tadahiro (The Copernicus Journal of Political Studies, 2025)
The advent of the Truman Doctrine in 1947 was a historical moment in US foreign policy, which brought a significant change of approach from traditional isolationism to internationalism. Those who vehemently opposed this unprecedented policy were congressional isolationists. The article analyzes how and why the isolationists’ policy was abandoned after the Truman Doctrine was established. It can be stated that the downfall of isolationists was a process determined by the international actions of the USSR and the US’ reaction. The main reason the isolationists changed their view was, on the one hand, the Truman administration’s anti-Soviet policy, and on the other, a compromise approach of government administration to budget expenditures on support to the different countries, tailored to isolationists’ preference. The paper is focused on almost two years of the early Truman’s presidency until the signing of the Truman Doctrine (1945-1947). The primary method of research is content analysis and process tracing.